2019
DOI: 10.1051/e3sconf/201910000038
|View full text |Cite
|
Sign up to set email alerts
|

Power distribution in multi-motor (AWD) powertrain of electric vehicle

Abstract: This article presents the results of analysis of power distribution in an electric vehicle independent all-wheel drive. The utilized method of velocity distribution takes into account the change in the motion resistance occurring on particular wheel. Moreover, the method of determining the change of vertical loads on traction wheels is also described. Theoretical considerations were verified on a dedicated laboratory stand that allows to perform real time simulation for analysed powertrain structure. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…During this research it was observed that in the case of braking with the force of 150 N applied to the brake pedal, the amount of recovered energy is approximately 40% higher than when braking with the force of 400 N. According to the research carried out by the authors of papers [16,33,38], properly adjusted force on the brake pedal, the depth and time of pressing the brake pedal during braking can affect the comfort of braking and the efficiency of regeneration. This is obvious, because in most electric vehicle braking systems, the first system to be activated is the electrical system which converts kinetic energy into electric energy using the electric machine [15]. The amount of recovered energy is limited by the current-voltage characteristic of the electric machine and the battery.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…During this research it was observed that in the case of braking with the force of 150 N applied to the brake pedal, the amount of recovered energy is approximately 40% higher than when braking with the force of 400 N. According to the research carried out by the authors of papers [16,33,38], properly adjusted force on the brake pedal, the depth and time of pressing the brake pedal during braking can affect the comfort of braking and the efficiency of regeneration. This is obvious, because in most electric vehicle braking systems, the first system to be activated is the electrical system which converts kinetic energy into electric energy using the electric machine [15]. The amount of recovered energy is limited by the current-voltage characteristic of the electric machine and the battery.…”
Section: Conclusion and Discussionmentioning
confidence: 99%